School Experiences of Gifted Adolescents and Their Peers - Carter, Shannon Sines; Avci, Ayse Hilal; Mammadov, Sakhavat (Psychology in the schools, 2025)
ABSTRACT This study examined the school experiences of gifted adolescents and their non‐identified peers. Cross‐sectional data were obtained from 748 middle and high school students from a large public school district in the Southeastern United States. Students reported on their behavioral and emotional engagement and disaffection, relationships with teachers and peers, social adjustment, and sense of belonging. Gifted students also responded to questions about their perceived social stigma related to giftedness. No multivariate or univariate group differences were found between gifted and non‐identified students on the study measures. However, not all gifted students had similar school experiences, particularly in relation to feelings of social stigma. About one‐third of the gifted students reported experiencing some degree of stigma. These students had lower teacher‐student relationships (p < 0.001, Cohen's d = 0.84), weaker peer support (p < 0.01, Cohen's d = 0.63), lower social adjustment (p < 0.01, Cohen's d = 0.58), and a lower sense of belonging (p < 0.001, Cohen's d = 0.10) compared to other gifted students who experienced little or no stigma. Findings are discussed in the context of gifted education and their implications for educational practice. Summary School experiences of gifted students may not differ substantially from those of other students. Some gifted students may experience social stigma. Social stigma of giftedness is associated with weaker relationships with teachers and peers, lower social adjustment, and a reduced sense of belonging.